Associations between homocysteine, vitamin B12, and folate and the risk of all-cause mortality in American adults with stroke - Zhang, Panpan; Xie, Xia; Zhang, Yurong (Frontiers in Nutrition, 2023)
Objective Associations between plasma homocysteine (Hcy), vitamin B12, and folate and the risk of all-cause mortality are unclear. This study aimed to examine whether plasma Hcy, vitamin B12, and folate levels independently predict the risk of all-cause mortality in American adults with stroke. Methods Data from the United States National Health and Examination Survey (NHANES; 1999–2006) were used and linked with the latest (2019) National Death Index (NDI). Cox proportional hazards models and restricted cubic splines were used to estimate the hazard ratios (HR) and 95% confidence intervals (CI) of all-cause mortality for Hcy, folate, and B12 levels in adults with stroke. Sample weights were calculated to ensure the generalizability of the results. Results A total of 431 participants were included (average age: 64.8 years). During a median follow-up of 10.4 years, 316 deaths occurred. Hcy was positively associated with all-cause mortality in adults with stroke (HR, 1.053; 95% CI: 1.026–1.080). Stroke patients with plasma Hcy levels in the fourth quartile had a 1.631-fold higher risk of all-cause mortality (HR, 1.631; 95% CI: 1.160–2.291) than those in the first quartile. The association between plasma Hcy and all-cause mortality was strong significant in older patients (p for interaction = 0.020). Plasma folate and vitamin B12 concentrations were inversely correlated with Hcy concentrations [B-value (95% CI): −0.032 (−0.056– −0.008), −0.004 (−0.007– −0.002), respectively]. No significant associations were observed between folate, vitamin B12 levels, and all-cause mortality in adults with stroke. Conclusion Plasma Hcy levels were positively associated with all-cause mortality in older adults with stroke. Folate and vitamin B12 levels were inversely correlated with Hcy. Plasma Hcy may serve as a useful predictor in mortality risk assessment and targeted intervention in adults with stroke.